Análise da estabilidade de pequenas centrias hidrelétricas em operação isolada - Karnikowski, Douglas de Castro (2016)
Islanding occurs when a part of the electrical system is supplied solely by a unit or group of distributed generators isolated from the main electrical network. When the center of Distributed Generation (DG) operates connected to the electrical system, the stability depends especially on the inertia of the large power generation plants. However, when DG operates in isolation, the stability depends on the response from controllers, the dynamics of the turbine and generator to maintain the system in normal operation. Due to the low inertia of the isolated system, the network is more susceptible to sags or swells and violations in the frequency levels. Thus, this work aims to analyze the stability of systems with DG operating in isolation, making sure that it can keep the stress levels and appropriate frequency. Dynamic simulation system are performed in Matlab Simulink® environment using the SimPowerSystems library, where the case study is carried out with a DG type Small Hydroelectric Plant (SHP), analyzing the stability of microgrid upon disconnection with the system main and stand-alone operation (load shedding, load connection, short circuit, among other contingencies). It is also observed the behavior of the microgrid in cases of restoration of power supply through the start of DG operating in isolation.